Molecular mechanisms of seed dormancy release by gas plasma-activated water technology - Grainge, Giles; Nakabayashi, Kazumi; Steinbrecher, Tina; Kennedy, Sue; Ren, Junchen; Iza, Felipe; Leubner-Metzger, Gerhard (Journal of experimental botany, 2022)
Developing innovative agri-technologies is essential for the sustainable intensification of global food production. Seed dormancy is an adaptive trait which defines the environmental conditions in which the seed is able to germinate. Dormancy release requires sensing and integration of multiple environmental signals, a complex process which may be mimicked by seed treatment technologies. Here, we reveal molecular mechanisms by which non-thermal (cold) atmospheric gas plasma-activated water (GPAW) releases the physiological seed dormancy of Arabidopsis thaliana. GPAW triggered dormancy release by synergistic interaction between plasma-generated reactive chemical species (NO3-, H2O2, ·NO, and ·OH) and multiple signalling pathways targeting gibberellin and abscisic acid (ABA) metabolism and the expression of downstream cell wall-remodelling genes. Direct chemical action of GPAW on cell walls resulted in premature biomechanical endosperm weakening. The germination responses of dormancy signalling (nlp8, prt6, and dog1) and ABA metabolism (cyp707a2) mutants varied with GPAW composition. GPAW removes seed dormancy blocks by triggering multiple molecular signalling pathways combined with direct chemical tissue weakening to permit seed germination. Gas plasma technologies therefore improve seed quality by mimicking permissive environments in which sensing and integration of multiple signals lead to dormancy release and germination.
Keywords: proteiny huseníčku; semena rostlinná; non-thermal atmospheric gas plasma technology; Plant Dormancy; technologie; Arabidopsis thaliana; Abscisic Acid; Arabidopsis; klíčení; voda; Arabidopsis Proteins; Germination; Abscisic acid metabolism; nitrogen signalling; peroxid vodíku; Seeds; Hydrogen Peroxide; vegetační klid; regulace genové exprese u rostlin; gas plasma-activated water; seed dormancy; Gene Expression Regulation, Plant; plant hormone signalling; reactive oxygen species; endosperm weakening; kyselina abscisová; Water; Technology